Factors influencing the adoption of climate change adaptation samong rice growers in Doi Saket District, Chiang Mai Province, Thailand - R. Sirisunyaluck (2020)
© 2020 Association of Agricultural Technology in Southeast Asia. All rights reserved. The factors influencing the adoption of climate change adaptation strategies among rice growers in Doi Saket district were investigated. A proportionate stratified random sampling technique was reported from 200 rice growers as respondents from 13 sub-districts of Doi Saket district. It was observed that the majority of the rice growers adopted some climate change adaptation strategy such as changing planting date and growing different types of crops. Three variables, the cost per unit of planting, revenue sources and group membership were significant influenced in the adoption of climate change adaptation strategies at p ≤ 0.05. However, only a few adaptation strategies were adopted. Thus, information on climate change and its impact as well as adaptation strategies should be disseminated to the rice growers. Training on these issues should be organized for agricultural extension officers so that they can be actived to support the rice growers. To support these farmers, research findings to improve rice varieties with drought-tolerance, and improvement of irrigation system efficiency should be implemented.